PENJADWALAN PENGIRIMAN PRODUK KAOS OLEH C.V. CHRONICLE MART KEPADA SUB DISTRIBUTOR CIANJUR DENGAN MENGUNAKAN METODA DRP (DISTRIBUTION REQUIREMENT PLANNING) - akhmad sutoni (Politeknik APP Jakarta, 2017)
Pattern of market demand for company C.V. Chronicle Mart in each period is not constant, always changing. The Company also faces competition with companies engaged in similar fields in order to meet market demand. Production planning activities are the company's strategy in conducting its production process to face the changing market demand. The company has problems with the quantity of goods production and distribution system that compete well, such as delivery time, quantity, and type of goods delivered, resulting in shortage or excess inventory. Method for planning and scheduling of distribution activity is by using DRP (Distribution Requirement Planning) with order policy using EOQ (Economic Order Quantity). In this research, we get the optimum cost of 103,265,000 rupiah in a year